Chronic obstructive pulmonary disease: Management of chronic disease - Russell, R; Norcliffe, J; Bafadhel, M (2012)
Chronic obstructive pulmonary disease (COPD) is the disease that has been described as the epidemic of our time. Cigarette smoking is the major cause of the disease and smoking cessation is the most effective intervention in both preventing disease development and progression. Once established, COPD causes irreversible airways obstruction that often results in breathlessness. The management of this condition involves initially an accurate diagnosis and a clinical and functional assessment. The primary confirmatory investigation is spirometry, although other tests such as chest X-ray are helpful in excluding other diseases. Treatment is aimed at preventing acute attacks (exacerbations) of disease and stopping disease progression. After smoking cessation, the most effective therapy is pulmonary rehabilitation, a multidisciplinary series of exercise and education sessions, which have been shown to be clinically and cost effective. Drug therapy reduces breathlessness and reduces attack rates. An effective approach to COPD requires cooperation of all healthcare providers working across primary and secondary care boundaries. Many agencies will and should be involved, including GPs, palliative care services, district nurses, hospital specialist services and social services. Patients can be educated about their disease and empowered to self manage, so that they can use health service providers in a more effective manner. © 2012 Elsevier Ltd. All rights reserved.